A MODEL OF ANALYSIS FOR THE EVALUATION OF TOURIST DESTINATION APPEAL: THE AMALFI COAST. A CASE STUDY - Antonio Botti; Salvatore Esposito de Falco; Massimiliano Vesci (Enlightening Tourism: A Pathmaking Journal)
Core resources and attractors have long been at the center of studies on the competitiveness of tourist destinations. However, such studies treat factors of appeal in a cumulative way without, or at least rarely, integrating the perspectives of both supply and demand. Our paper intends to verify whether the scale of importance of the attractors detains an absolute value or whether such value varies on the basis of type of destination. The study proposes a model of analysis of destination appeal which takes into account the perception that both hotel management and potential tourists have of such attractors.